Subnanomolar Detection of Oligonucleotides through Templated Fluorogenic Reaction in Hydrogels: Controlling Diffusion to Improve Sensitivity. Issue 19 (6th April 2017) - Al Sulaiman, Dana; Chang, Jason Y. H.; Ladame, Sylvain
Abstract: Oligonucleotide‐templated reactions are valuable tools for nucleic acid sensing both in vitro and in vivo. They are typically carried out under conditions that make any reaction in the absence of template highly unfavorable (most commonly by using a low concentration of reactants), which has a negative impact on the detection sensitivity. Herein, we report a novel platform for fluorogenic oligonucleotide‐templated reactions between peptide nucleic acid probes embedded within permeable agarose and alginate hydrogels. We demonstrate that under conditions of restricted mobility (that is, limited diffusion), non‐specific interactions between probes are prevented, thus leading to lower background signals. When applied to nucleic acid sensing, this accounts for a significant increase in sensitivity (that is, lower limit of detection). Optical nucleic acid sensors based on fluorogenic peptide nucleic acid probes embedded in permeable, physically crosslinked, alginate beads were also engineered and proved capable of detecting DNA concentrations as low as 100 pm . Abstract : Nucleic acid hydrogel sensor : The subnanomolar detection of nucleic acid targets driven by an oligonucleotide‐templated reaction between embedded fluorogenic peptide nucleic acid probes is demonstrated. Restricting probe diffusion in physically crosslinked hydrogels significantly increases the detection sensitivity by reducing non‐specific reactions between probes in the absence of the target.